2012
DOI: 10.1371/journal.pone.0052271
|View full text |Cite
|
Sign up to set email alerts
|

Long CAG Repeat Sequence and Protein Expression of Androgen Receptor Considered as Prognostic Indicators in Male Breast Carcinoma

Abstract: BackgroundThe androgen receptor (AR) expression and the CAG repeat length within the AR gene appear to be involved in the carcinogenesis of male breast carcinoma (MBC). Although phenotypic differences have been observed between MBC and normal control group in AR gene, there is lack of correlation analysis between AR expression and CAG repeat length in MBC. The purpose of the study was to investigate the prognostic value of CAG repeat lengths and AR protein expression.Methods81 tumor tissues were used for immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Conversely, the evaluation of sex hormone receptor status in a series of 39 patients suggested that 5-year diseasefree survival and overall survival were significantly shorter for patients with AR-positive tumors [44], as analogously noted in a cohort examining 102 MBC patients where AR-expressing MBC patients apparently derived a lower benefit from tamoxifen [45]. An association between AR expression and longer CAG repeats was also reported negatively impacting survival outcomes [27]. Conversely, in one of the largest series presented so far AR-positive luminal A MBC had improved overall survival compared with matched FBC cases [46].…”
Section: Ar In Mbc: Expression Levels and Clinical Outcomesmentioning
confidence: 84%
See 1 more Smart Citation
“…Conversely, the evaluation of sex hormone receptor status in a series of 39 patients suggested that 5-year diseasefree survival and overall survival were significantly shorter for patients with AR-positive tumors [44], as analogously noted in a cohort examining 102 MBC patients where AR-expressing MBC patients apparently derived a lower benefit from tamoxifen [45]. An association between AR expression and longer CAG repeats was also reported negatively impacting survival outcomes [27]. Conversely, in one of the largest series presented so far AR-positive luminal A MBC had improved overall survival compared with matched FBC cases [46].…”
Section: Ar In Mbc: Expression Levels and Clinical Outcomesmentioning
confidence: 84%
“…Two studies searching for an association between CAG repeat length and MBC did not notice any appreciable differences between cases and the respective control groups [22,25]. Two other studies suggested that longer CAG repeats are more common in MBC that in controls [26,27], and a trend toward a higher frequency of shorter CAG tracts in the control group emerged from a fifth report [28]. Thus, even though genetic evidence is scarce and somewhat ambiguous, the scenario proposed is that androgen hyposensitivity caused by either AR mutations or long CAG repeats might be a causal factor for MBC.…”
Section: Ar In Mbc: Genomicsmentioning
confidence: 99%
“…For example, the androgen signal provides a mitogenic effect in the prostate, where decreasing CAG repeat length of the AR gene increases the cancer risk. By contrast, androgens in breast tissues function in an antimitogenic response, in which long CAG repeats indicated a higher risk for male (14) and female (15) patients with breast cancer. Finally, we observed that the colorectal cancer group had a longer CAG repeat length compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…AR-Forward was fluorescently labeled with 6-carboxyfluorescine (FAM). PCR was carried out as we have previously described (14). Data were analyzed by GeneScan Software (Applied Biosystems) and Genetyper Software (Applied Biosystems).…”
Section: Pcr-based Genescan Analysis Of Ar Cag Repeats Lengthmentioning
confidence: 99%
“…Breast cancer tissue microarrays (TMA) were used as described previously [23, 24] and immunohistochemically stained for AR, ER, PR, Her2, Ki67 and β-catenin expression levels. Briefly, after deparaffinization, sections were hydrated and underwent Ethylene Diamine Tetraacetic Acid (EDTA) buffer (pH 8.0) or sodium citrate buffer (pH 6.0) retrieval.…”
Section: Methodsmentioning
confidence: 99%